PENGARUH EARNINGS PER SHARE (EPS), RETURN ON EQUITY (ROE), RETURN ON ASSETS (ROA), DAN NET PROFIT MARGIN (NPM) TERHADAP HARGA SAHAM (Studi pada Perusahaan Property dan Real Estate yang terdaftar di Bursa Efek Indonesia tahun 2014-2018) - Faisol, Ahmad (JURNAL RISET AKUNTANSI JAMBI, 2019)
Investment in the capital market is a form of investment that is profitable but also high risk, so investors in investing need accurate information so that they are not trapped in adverse conditions. This information is used to find out variables that can affect stock price fluctuations. This study aims to determine the effect of EPS, ROE, ROA, and NPM on stock prices. This research was conducted by explanatory research method with a quantitative approach, where the data used in the form of secondary data. The population in this study were Property and Real Estate companies listed on the Indonesia Stock Exchange in 2014-2018, which numbered 50 companies. The number of samples used was 21 companies with Purposive Sampling techniques. The method of data analysis uses multiple linear regression analysis which is processed with SPSS. The results of this study indicate that the effect of EPS, ROE, ROA and NPM tested on stock prices shows that the value of tcount is (9,401> 1,984), (2,645> 1,984), (2,163> 1,984) and (0.009 <1,984) with the probability level significance with a significance level of 0.05. It can be concluded that partially the EPS ROE variable and ROA have an influence on the stock prices of Property Companies and real estate listed on the Indonesia Stock Exchange in 2014-2018. While the NPM variable has no influence on the stock prices of Property Companies and real estate listed on the Indonesia Stock Exchange in 2014-2018. Based on the F Test above, it shows that the Fcount is 31.581 while Ftable is 2.46 with a significance level ? = 0.05. From these data indicate that Fcount> Ftable (31.581> 2.46) and probability of significance 0.000 <0.05. Then H5 is accepted and H0 is rejected, so it can be concluded that EPS (X1), ROE (X2), ROA (X3), and NPM (X4) variables simultaneously or jointly have a significant effect on the share price of Property Companies and real estate.